2022
DOI: 10.36922/gpd.v1i1.114
|View full text |Cite
|
Sign up to set email alerts
|

Gene-modified T cell therapy for cancer: Current challenges and potential solutions

Abstract: Immunotherapy has achieved significant breakthroughs in patients with hematological diseases and various cancers. The adoptive transfer of T cells, especially gene-modified T cells such as chimeric antigen receptor T (CAR-T) cells and T cell receptor-engineered T (TCR-T) cells, is developing rapidly. Since 2017, eight CAR-T cell products have been approved for the treatment of hematological diseases, such as refractory or relapsed acute B lymphoblastic leukemia, specific subtypes of B cell lymphoma, and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 106 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…Wang et al found through immunohistochemical analysis of TLR4 after SAH that TLR4 in neurons after SAH is significantly up-regulated [ 18 ]. Islam et al concluded through the analysis of TLR4-specific gene knockout in microglia, astrocytes and neurons in the SAH mouse model that TLR4 is expressed in microglia, and the activation of TLR4 in microglia after SAH can cause nerve injury [ 130 , 131 ]. Thus far, TLR4 up-regulation in neurons and microglia after SAH has been proven.…”
Section: Tlr4 Expression In Different Cells In the Central Nervous Sy...mentioning
confidence: 99%
“…Wang et al found through immunohistochemical analysis of TLR4 after SAH that TLR4 in neurons after SAH is significantly up-regulated [ 18 ]. Islam et al concluded through the analysis of TLR4-specific gene knockout in microglia, astrocytes and neurons in the SAH mouse model that TLR4 is expressed in microglia, and the activation of TLR4 in microglia after SAH can cause nerve injury [ 130 , 131 ]. Thus far, TLR4 up-regulation in neurons and microglia after SAH has been proven.…”
Section: Tlr4 Expression In Different Cells In the Central Nervous Sy...mentioning
confidence: 99%
“…Various biomarkers play a crucial role in diverse medical applications, including diagnosis, drug delivery, and therapeutics [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Biosensors, utilizing biological molecules or organisms, are employed to detect the presence of specific substances in biological fluids, facilitating the identification of biomarkers for disease diagnosis [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%